Trail log - 2022 - Rolston, Holmes, 1932-2025, author (Colorado State University. Libraries, 2022)
Summary: January, Disastrous wildfires near Boulder, Colorado. January, Tonga, the Hunga Tonga–Hunga Ha'apai Volcano erupted, largest atmospheric explosion in recorded history. Pasqueflowers at Easter. September, Queen Elizabeth's death, our memories of her in her youth, and of Prince Philip awarding me the Templeton Prize in Buckingham Palace in 2003. December, Mauna Loa erupting.
Keywords: personal narrative